Computerized Cognitive Testing for Older Adults: A Review. (February 2015) - Zygouris, Stelios; Tsolaki, Magda
Objective: This article is a review of computerized tests and batteries used in the cognitive assessment of older adults. Method: A literature search on Medline followed by cross-referencing yielded a total of 76 citations. Results: Seventeen test batteries were identified and categorized according to their scope. Computerized adaptive testing (CAT) and the Cambridge Cognitive Examination CAT battery as well as 3 experimental batteries and an experimental test are discussed in separate sections. All batteries exhibit strengths associated with computerized testing such as standardization of administration, accurate measurement of many variables, automated record keeping, and savings of time and costs. Discriminant validity and test–retest reliability were well documented for most batteries while documentation of other psychometric properties varied. Conclusion: The large number of available batteries can be beneficial to the clinician or researcher; however, care should be taken in order to choose the correct battery for each application.